2014
DOI: 10.5380/avs.v19i4.35581
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho E Características Morfo- Intestinais De Leitoas Desmamadas Alimentadas Com Dietas Contendo Associações De Mananoligossacarídeo

Abstract: RESUMO:Avaliou-se o efeito da suplementação de mananoligossacarídeo isolado e associados com ß-glucano e antibiótico em dietas de leitoas durante a fase de creche (21 aos 54 dias de idade) sobre o desempenho, características morfo-histológicas da mucosa intestinal e ocorrência de diarréia. Foram utilizadas 368 leitoas de mesma linhagem, com peso médio de 6,5 kg/unidade experimental, distribuídas em delineamento inteiramente casualizado com quatro tratamentos: 1 -Dieta controle Dieta basal -sem suplementação, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
2
2
0
3
Order By: Relevance
“…Similar results were observed by SANCHES et al (2006) and ASSIS et al (2014), who evaluated the inclusion of prebiotics β-glucan, or antibiotics in diets for weaned piglets and also reported no effect on CD in the duodenum and jejunum of pigs. However, HU et al (2013) observed shorter villus and deeper crypt on d 3 and 7 post-weaning, but according to these authors the damaged intestinal morphology was already recovered to preweaning values on day 14 post-weaning.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Similar results were observed by SANCHES et al (2006) and ASSIS et al (2014), who evaluated the inclusion of prebiotics β-glucan, or antibiotics in diets for weaned piglets and also reported no effect on CD in the duodenum and jejunum of pigs. However, HU et al (2013) observed shorter villus and deeper crypt on d 3 and 7 post-weaning, but according to these authors the damaged intestinal morphology was already recovered to preweaning values on day 14 post-weaning.…”
supporting
confidence: 78%
“…Similarly, SANCHEZ (2006) reported no effect on ADFI of piglets from 23 to 58 days of age fed diets containing antibiotics, probiotics (Bacillus subtilis), prebiotics (MOS), and symbiotic. In a study to assess the inclusion of sodium butyrate (0.1, 0.2 and 0.4%) in diets for pigs weaned at 28 days of age, ASSIS et al (2014) evaluated diets containing mannanoligosaccharides (MOS), beta-glucans and antibiotics for gilts from 21 to 34 days of age and also reported no effect on ADFI.…”
Section: Resultsmentioning
confidence: 99%
“…The results match those reported by Grela et al (2006), who, when assessing the frequency of diarrhea in piglets from birth to 84 days of age, found that adding 3,000mg/kg and 5,000mg/kg mannanoligosaccharide and fructooligosaccharide, respectively, decreased diarrhea incidence. Such results are attributed to the possible improvement of the immune system and epithelium integrity (Wu et al, 2017) and match the findings by Budiño et al (2010), Assis et al (2014), andLuna et al (2015), who used fructooligosaccharides, mannanoligosaccharides, and β-glucans + mannanoligosaccharides versus GPA respectively, and found no differences among the treatments.…”
Section: Resultssupporting
confidence: 89%
“…Os prebióticos também são aditivos, porém são ingredientes que não são digeridos pelas enzimas presentes no trato gastrointestinal dos animais, todavia, são fermentados pelas bactérias e gera substancias que estimulam o crescimento e atividade de bactérias benéficas para o hospedeiro, inibindo assim o crescimento e colonização de bactérias patogênicas (Assis et al, 2014& Sessin, 2018) Brito et al, (2013, citam em sua revisão que o efeito do aditivo probiótico e prebiótico sobre desempenho de leitões desmamados aos 23 dias mostraram que essa adição proporcionou desempenho dos animais semelhantes quando comparado ao tratamento com antibióticos. O seu uso ainda melhorou a qualidade da carcaça, apresentando uma carne com menor perda de água durante o processo de cozimento, melhor retenção e firmeza da carne.…”
Section: Influência Dos Aditivos Na Saúde Intestinal Dos Suínosunclassified